Collateral damage: trade disruption and the economic impact of war - Alan M. Taylor; Reuven Glick (University of California, Department of Economics, 2005)
Conventional wisdom in economic history suggests that conflict between countries can be enormously disruptive of economic activity, especially international trade. Yet nothing is known empirically about these effects in large samples. We study the effects of war on bilateral trade for almost all countries with available data extending back to 1870. Using the gravity model, we estimate the contemporaneous and lagged effects of wars on the trade of belligerent nations and neutrals, controlling for other determinants of trade. We find large and persistent impacts of wars on trade, and hence on national and global economic welfare. A rough accounting indicates that such costs might be of the same order of magnitude as the direct costs of war, such as lost human capital, as illustrated by case studies of World War I and World War II.
Keywords: D74; F02; F10; F14; H56; N40; N70; 330